SCHEMA THEORY IN READING CLASS - Fahriany Fahriany (IJEE (Indonesian Journal of English Education), 2014)
Comprehension is making a sense out of text. It is a process of using reader’s existing knowledge (schemata) to interpret texts in order to construct meaning. Many reading experts agree that the schema theory is one of the reasonable theories of human information processing. Schemata, the plural of schema, are believed to be the building blocks of cognition. This paper discusses the role of readers’ preexisting knowledge on linguistics code as well as readers’ knowledge of the world (schema), which for the case of reading has similar importance of the printed words in the text. It is argued that the more non visual information the reader posses, the less visual information is needed. For teaching and learning, teachers are expected to use different strategies in order to deal with different students’ preexisting knowledge and schema to maximize students’ learning.